Analisis Kandungan Nutrisi Bekas Maggot (Kasgot) Sebagai Pupuk Organik Berkualitas - Alif Al Furqan, Muh.; Iryani, A. Sry (Jurusan Kimia FMIPA UNM, 2025)
Agriculture is a very important sector in the country's economy where one of the things that affects agricultural productivity is fertiliser. Fertiliser scarcity is a serious problem and has an impact on the agricultural sector. As an alternative, the community makes organic fertiliser by utilising maggot technology to decompose organic waste (leaves, fruit scraps, kitchen waste and others) from the decomposition results will produce food waste from maggot which is called kasgot where this kasgot is used as organic fertiliser for various agricultural plants. The purpose of this research was conducted to determine the nutritional content of the former maggot (kasgot). The methods used in this research are qualitative and quantitative as well as the instrument chemical analysis method in determining the nutrient content in fertiliser from ex-maggot (kasgot). The results concluded that the former maggot (kasgot) fertiliser contained quite high nutrients, namely C-Organic 4.19%; Moisture Content 42.71%; pH 7.50; C/N Ratio 0.34; Nitrogen (N) 12. 50%; Phosphorus (P2O5) 12.09%; Potassium (K2O) 17.25%; Iron (Fe) total 0.1526 ppm; Zinc (Zn) total 0.0521 ppm; Arsenic (As) < 0.001 ppm; Lead (Pb) 0.027 ppm; Mercury (Hg) < 0.008 ppm. This study concluded that spent maggot (kasgot) can be used as an economical and ecological alternative to organic fertiliser to increase crop productivity.